A Case of a 4-Year-Old Carbon Baby: Acquired Universal Melanosis and Literature Review: Carbon baby - ., Amisha; Malik, Paras; Pathania, Monika; Rathaur, Vyas Kumar (International Journal of Innovative Research in Medical Science, 2020)
Disorders of color variation can be localized or generalized, congenital or acquired, acute or chronic. Among the various causes of generalized skin darkening encountered in the pediatric age group, acquired universal melanosis aka Carbon Baby Syndrome is an uncommon hypermelanotic condition, with a histologic appearance of extensive epidermal melanization. The authors report one such case of a 4-year old boy with progressive darkening of skin starting at the age of 1 year and involving the entire body surface in the absence of any other systemic alterations. The disease prevalence, etiology, mechanism and prognosis are still unknown.